Ketidakcukupan konsumsi pangan perempuan kawin dan intensi fertilitas - Simamora, Hot Nauli; Setyonaluri, Diahhadi (Jurnal Kependudukan Indonesia, 2025)
The correlation between undernourished status and fertility intention is complex, influenced by biological and behavioural mechanisms due to malnutrition. This study aims to analyse the relationship between the undernourished status of married women aged 15-49 years and their desire to have or add children (fertility intention). A quantitative analysis was conducted using secondary data from the 2021 National Socio-Economic Survey, analysed through descriptive and ordinal logistic regression methods. The results indicate that nearly half of married women in Indonesia are undernourished in terms of their energy and protein intake. Inferential analysis reveals a significant correlation between fertility intention and the malnutrition status of married women. Undernourished women exhibit lower fertility intentions compared to well-nourished women. Additionally, there is a notable difference in the relationship between calorie and protein consumption status and fertility intention levels when considering women’s parity, after controlling for individual, couple, and household characteristics. The findings implicate that the government should encourage undernourished women to use contraceptives until their nutritional intake is sufficient, ensuring they are physically and mentally prepared for pregnancy.